2018
DOI: 10.1063/1.5054999
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale domains in ionic liquids: A statistical mechanics definition for molecular dynamics studies

Abstract: One of the many open questions concerning Ionic Liquids (ILs) is the existence of nanoscale supra-molecular domains which characterize the bulk. The hypothesis of their existence does not meet a general consensus since their definition seems to be based on ad hoc arbitrary criteria rather than on general and solid first principles of physics. In this work, we propose a suitable definition of supra-molecular domains based on first principles of statistical mechanics. Such principles can be realized through the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In molecular simulations, the concept of a system's hydration shell is usually defined in terms of empirical geometric criteria, such as the the first minimum of a radial distribution function [3]; however, such kinds of definitions do not provide precise details about the most relevant microscopic degrees of freedom that characterize interface properties. In a recent work on ionic liquids [4], our group has proposed a statistical mechanics definition of nanodroplets: the size of a droplet is defined as the size of the region where atomistic degrees of freedom are strictly required while the effect of the rest of the liquid can be modeled as a structureless, macroscopic thermodynamic reservoir. Such a definition highlights the relevance of the chemical molecular degrees of freedom and their range of action for a given structural property-they are sufficient to describe local liquid properties independently of any structural support from the bulk.…”
Section: A Hydration Shell In Biological Membranesmentioning
confidence: 99%
“…In molecular simulations, the concept of a system's hydration shell is usually defined in terms of empirical geometric criteria, such as the the first minimum of a radial distribution function [3]; however, such kinds of definitions do not provide precise details about the most relevant microscopic degrees of freedom that characterize interface properties. In a recent work on ionic liquids [4], our group has proposed a statistical mechanics definition of nanodroplets: the size of a droplet is defined as the size of the region where atomistic degrees of freedom are strictly required while the effect of the rest of the liquid can be modeled as a structureless, macroscopic thermodynamic reservoir. Such a definition highlights the relevance of the chemical molecular degrees of freedom and their range of action for a given structural property-they are sufficient to describe local liquid properties independently of any structural support from the bulk.…”
Section: A Hydration Shell In Biological Membranesmentioning
confidence: 99%
“…The interface of these regions is characterized by a transition region where interactions, via a spacedependent switching function, smoothly change from atomistic to coarse-grained and vice versa. The method has been applied with success to several challenging systems, including solvation of large molecules [36][37][38][39][40][41] and ionic liquids [42][43][44] to cite a few. Recent developments of the method have shown that changing resolution through a space-dependent function slows computational performance and is overall not convenient for the implementation of the algorithm or its transferability from one code to another.…”
mentioning
confidence: 99%
“…One example is ionic liquids, where electrostatics plays a major role. The AdResS approach was shown to describe such liquids in equilibrium in a highly satisfactory manner, [ 22–24 ] and it will be interesting, in perspective, to test whether the current non‐equilibrium set up of AdResS would be directly applicable to ionic liquids in a thermal gradient, or whether modifications at the coupling boundaries are needed.…”
Section: Discussionmentioning
confidence: 99%